QUALITATIVE CONTENT ANALYSIS OF PUBLIC STATEMENTS ABOUT THE “SERBIAN WORLD” CONCEPT: A CRITICAL REVIEW BY ITS OPPONENTS - Ljubomirović, Aleksandar (Political Review, 2024)
This article aims to present the outcomes of the research on the way how the “Serbian world” concept is perceived by its opponents. This represents a particularly significant approach for better understanding and an essential step closer to defining the concept within scientific frameworks, given that it was popularized more by its opponents than its propagators. The methodology used in this paper includes a qualitative content analysis of public statements by leading non-Serbian (Western and regional) social actors who openly criticized the “Serbian world” in their public appearances. Simultaneously, the analysis of the concept is limited to observing the way it is seen by its opponents, using their statements as examples of the discursive construction of reality. This methodological approach is significant to understanding the “Serbian world” concept because it is mainly a mental construct, and the focus will thus also be on how the leading opponents mentally shape the world around them, as well as on the process of conceptualization of reality. Based on the research carried out, the author concludes that the statements of the leading opponents of the “Serbian world” indicate that for them, there is only one dimension of the concept, namely the territorial. According to their statements, that component of the concept was taken from the already existing “Russkiy mir” concept, serves to implement the foreign policy interests of the Russian Federation in the Balkans, and is based on the greater-state aspirations of the Serbian political leadership and the unrealized “Greater Serbia” idea. Finally, given that the concept is relatively unexplored, the paper aims to present perspectives for further research on the phenomenon.